Leaf and tree responses of young European aspen trees to elevated atmospheric CO2 concentration vary over the season. (6th April 2021) - Lauriks, Fran; Salomón, Roberto Luis; De Roo, Linus; Steppe, Kathy
Abstract: Elevated atmospheric CO2 concentration (eCO2 ) commonly stimulates net leaf assimilation, decreases stomatal conductance and has no clear effect on leaf respiration. However, effects of eCO2 on whole-tree functioning and its seasonal dynamics remain far more uncertain. To evaluate temporal and spatial variability in eCO2 effects, 1-year-old European aspen trees were grown in two treatment chambers under ambient (aCO2, 400 p.p.m.) and elevated (eCO2, 700 p.p.m.) CO2 concentrations during an early (spring 2019) and late (autumn 2018) seasonal experiment. Leaf (net carbon assimilation, stomatal conductance and leaf respiration) and whole-tree (stem growth, sap flow and stem CO2 efflux) responses to eCO2 were measured. Under eCO2, carbon assimilation was stimulated during the early (1.63-fold) and late (1.26-fold) seasonal experiments. Stimulation of carbon assimilation changed over time with largest increases observed in spring when stem volumetric growth was highest, followed by late season down-regulation, when stem volumetric growth ceased. The neutral eCO2 effect on stomatal conductance and leaf respiration measured at leaf level paralleled the unresponsive canopy conductance (derived from sap flow measurements) and stem CO2 efflux measured at tree level. Our results highlight that seasonality in carbon demand for tree growth substantially affects the magnitude of the response to eCO2 at both leaf and whole-tree level.